PERLINDUNGAN HUKUM TERHADAP FRANCHISEE YANG DI RUGIKAN OLEH FRANCHISOR DALAM PERJANJIAN WARALABA - Dwi Puji Astutik (RechtIdee, 2020)
Problems that often occur in practice of franchise agreements in Indonesia wich is often the franchise receiver and franchise giver in conducting cooperation agreements do not involve the role of a notary public in making the agreement so that the form of the agreement made is only an underhand agreement, it is very detrimental and creates risks if one party violates the agreement that has been agreed upon. The agreement made by both parties is no exception the franchise agreement which is made is only a limited agreement under the hand so that the protection of the rights of each party in the franchise agreement, especially the franchisee is not enough to protect the rights attached to him, because agreements made only under the hands of the strength of proof are not perfect, unlike agreements made authentically before a notary whose proof of strength is perfect. Therefore, in practice there are still many franchisees whose are harmed by the franchise agreement agreed upon with the franchisor. This research is normative using the statutory approach and the conceptual approach. The source of legal material in this study uses primary legal material sources supported by secondary legal materials and uses legal material collection techniques through library research, the analysis in this study uses content analysis and systematic interpretation. The results showed that legal protection in franchising activities (Franchise) is regulated in Government Regulation Number 42 of 2007 concerning Franchising. The form of this cooperation agreement is outlined in the form of a written agreement that contains several standard and additional clauses that have been discussed previously between the two parties. , this is what limits the franchisee by stating that after the termination of the agreement, the franchisee is limited to not doing business in a similar business to the previous franchise business that has been undertaken for a certain period. To protect the rights of the franchisee, the franchise agreement agreed upon must be in the form of a notary deed (authentic). It aims to ensure justice sbetween the parties and legal certainty of the contents of the franchise agreement more secure.